2022
DOI: 10.3389/fpsyg.2021.768372
|View full text |Cite
|
Sign up to set email alerts
|

Flow With Nature Treatment for Depression: Participants’ Experiences

Abstract: This study examined Flow with Nature (FWN) treatment, which is an integrative intervention (rehabilitation) based on eco and environmental psychology, psychotherapeutic theories and professional psychological practice. FWN is intended for depression rehabilitation with the help of social support, nature environments and FWN exercises. Exercises encourage sensing the environment, mindful awareness, psychological processing and focusing on the future. The FWN treatment proceeds in separate stages (horizon, growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Nevertheless, the use of virtual environments within NBIs may address some of the barriers to engagement discussed above, particularly for those who are unable to access real-life nature environments. For example, a recent study that was interrupted by the COVID-19 restrictions also found that conducting many elements of NBIs remotely also had therapeutic gain for participants with depression [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of virtual environments within NBIs may address some of the barriers to engagement discussed above, particularly for those who are unable to access real-life nature environments. For example, a recent study that was interrupted by the COVID-19 restrictions also found that conducting many elements of NBIs remotely also had therapeutic gain for participants with depression [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, building on the Restorative Cities Framework ( Roe and McCay, 2021 ), design interventions in the urban context can offer or stimulate activities that proved to be beneficial for mental health and wellbeing. These include for example physical activity ( Tamminen et al, 2020 ), exercises in mindfulness ( Davidson et al, 2003 ), contact with nature (e.g., Alvarsson et al, 2010 ; Ryan et al, 2014 ; Salonen et al, 2022 ), and social interaction ( Umberson and Montez, 2010 ). Additionally, urban design interventions can provide information on prevention of mental health issues such as stress reduction.…”
Section: Conceptual Framework For Fostering Urban Mental Health and M...mentioning
confidence: 99%
“…Depende del momento en que la persona decida establecer el contacto con la naturaleza y sus objetivos. Al respecto, hay evidencia de intervenciones efectivas para la depresión, en adultos que han usado la naturaleza como parte del tratamiento, y han encontrado disminución significativa de la sintomatología depresiva y aumento del bienestar mental positivo (Korpela et al, 2016;Salonen, 2022).…”
Section: El Papel Del Contexto En La Regulación Emocional De Los Adol...unclassified